Copper/Manganese Cocatalyzed Oxidative Coupling of Vinylarenes with Ketones - Lan, Xing-Wang; Wang, Nai-Xing; Zhang, Wei; Wen, Jia-Long; Bai, Cui-Bing; Xing, Yalan; Li, Yi-He (Organic letters, 2015)
A novel copper/manganese cocatalyzed direct oxidative coupling of terminal vinylarenes with ketones via C(sp3)–H bond functionalization following C–C bond formation has been developed using tert-butyl hydroperoxide as the radical initiator. Various ketones underwent a free-radical addition of terminal vinylarenes to give the corresponding 1,4-dicarbonyl products with excellent regioselectivity and efficiency through one step. A possible reaction mechanism has been proposed.